Alloy negative electrode of solid-state battery and preparation method of alloy negative electrode

By using two conductive carbon additives to coat the silicon active material in lithium-ion batteries and combining them with a hydride electrolyte to form a composite conductive carbon coating structure, the problem of battery efficiency reduction caused by changes in the volume of the silicon alloy is solved and higher efficiency is achieved. Conductivity and cycling performance.

CN119361705APending Publication Date: 2025-01-24NANJING UNIV OF AERONAUTICS & ASTRONAUTICS

Patent Information

Application Number
CN202411518988.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The volume of silicon alloy in lithium-ion batteries changes greatly during the lithiation/delithation process, resulting in a decrease in the efficiency of the electrode material and the rupture of the electrolyte interface, thereby reducing the initial Coulomb efficiency and cycling efficiency.

Method used

Two different conductive carbon additives, graphene and conductive graphite, through ball mill and thermal treatment technology, form a composite conductive carbon coated silicon -lodged substance, combined with the hydride electrolyte, forming three -dimensional tight electron/ion transmission network structure.

Benefits of technology

Improve the electrical conductivity and cycle performance, reduce the electrode polarization, alleviate the volume expansion of the silicon electrode during the cycle, and significantly improve the cycle stability and magnification performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361705A_ABST
    Figure CN119361705A_ABST
Patent Text Reader

Abstract

The invention discloses an alloy negative electrode of a solid-state battery and a preparation method of the alloy negative electrode, and belongs to the technical field of all-solid-state batteries, and the prepared alloy negative electrode can effectively improve the utilization rate of an active material, enhance the conductivity of a negative electrode material and reduce electrode polarization. The method comprises the following steps: pre-lithiating silicon powder to obtain lithium-silicon alloy powder A; mixing the conductive carbon B and the conductive carbon C, and performing ball milling to obtain mixed powder D; the lithium-silicon alloy powder A and the mixed powder D are mixed and subjected to ball milling, and mixed powder E is obtained; and adding an electrolyte into the powder E, mixing, and carrying out ball milling to obtain the alloy negative electrode material. The lithium ion battery assembled by adopting the alloy negative electrode has high first-circle coulombic efficiency, high charge-discharge capacity and excellent battery cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of all-solid-state batteries, and in particular relates to an alloy negative electrode of a solid-state battery and a preparation method thereof. Technical Background

[0002] At present, lithium-ion batteries are shining in the fields of consumer electronics and electric vehicles, and are gradually becoming the core technology in energy storage grids. However, the problem of lithium dendrites generated by the combination of lithium metal and traditional liquid electrolytes is still difficult to solve. Therefore, for safety reasons, replacing liquid electrolytes with solid electrolytes is the main research direction in the future. So far, many kinds of negative electrode materials have been studied, including alloys, oxides, etc. Silicon stands out among these materials due to its low alloying potential and theoretical capacity of up to 4200mAh / g. However, the large volume change of silicon alloys during the lithiation / delithiation process causes repeated contraction and expansion of silicon particles, which causes some silicon particles to pulverize and reduce efficiency; on the other hand, due to the repeated changes in the volume of silicon particles, the SEI layer at the electrolyte interface breaks, which reduces the initial coulomb efficiency and cycle efficiency. For high-capacity anode materials such as silicon, the first cycle lithium loss is even higher.

[0003] In order to solve the above problems, electrode pre-lithiation is a feasible method. Compared with the huge cyclic expansion stress of silicon, pre-lithiation silicon has lower volume expansion and superior ionic / electronic conductivity. However, when the lithium content in lithium-silicon alloy is low, the ionic / electronic conductivity of lithium-silicon alloy will be reduced. If the lithium content is too high, the growth of lithium dendrites and the risk of soft short circuit will increase. The ionic / electronic conductivity can be improved and the growth of lithium dendrites can be further inhibited by adding conductive additives. At the same time, conductive carbon can be in good contact with silicon, thereby effectively alleviating the volume expansion of silicon during the cycle and enhancing the cycle stability of silicon electrode. Different from the low deformability of oxide electrolytes, which leads to high interface resistivity between electrolyte and electrode and poor interface compatibility of sulfide electrolytes with lithium metal, hydrides have fast ionic conductivity and high reducibility and deformability, and are considered to be promising electrolytes. For example, in the patent CN118448584A, silicon powder, carbon material and binder are ball-milled and pressed into a film, and finally molten lithium is overturned with the silicon film to form a lithium-silicon alloy. The alloy prepared by this technology has only one carbon additive, which has little effect on inhibiting the volume expansion of the silicon negative electrode, and still causes a large amount of pulverization of the silicon negative electrode during the charge and discharge process. At the same time, there are still a large number of side reactions in the sulfide electrolyte and the alloy negative electrode, which leads to a sharp drop in battery capacity. Summary of the invention

[0004] The present invention provides an alloy negative electrode for a solid-state battery and a preparation method thereof. Based on the properties of different conductive carbons, the alloy negative electrode provided by the present invention with two different conductive carbon additions has high conductivity and charge and discharge capacity. The addition of composite conductive carbon effectively improves the utilization rate of electrode active materials, reduces electrode polarization, and further improves the cycle performance and rate performance of the silicon-based negative electrode.

[0005] To achieve the above object, the present invention adopts the following technical solutions: A method for preparing an alloy negative electrode of a solid-state battery comprises the following steps: S1, pre-lithiating silicon powder to obtain lithium-silicon alloy powder A; S2, mixing the conductive carbon B and the conductive carbon C, and ball milling them to obtain a conductive carbon mixed powder D; S3, mixing the lithium silicon alloy powder A and the mixed powder D, and ball milling to obtain a mixed powder E; S4. Add electrolyte to the mixed powder E, mix, and ball-mill to obtain an alloy negative electrode material.

[0006] In the above steps, the particle size range of the silicon powder used in S1 is 10~250nm; the mass ratio of silicon to lithium is 2.3~4.4; the lithium silicon alloy is subjected to the first heat treatment at a heating temperature of 200~800℃ for 15~60min, the second heat treatment at a heating temperature of 200~800℃ for 1~10h, and the third heat treatment at a heating temperature of 200~800℃ for 1~10h.

[0007] The conductive carbon B used in S2 is graphene, and the conductive carbon C is one or two of gas-phase carbon fiber, graphite, and carbon nanotubes; the mass ratio of the conductive carbon B to the conductive carbon C is 0.01-0.25; the hand grinding time before ball milling is 10-60 minutes; the ball-to-material ratio used in ball milling is 100:1, the ball milling speed is 50-1200rpm, and the ball milling time is 1-12 hours.

[0008] The mass ratio of alloy powder A and conductive carbon mixed powder D in S3 is 2~8; the hand grinding time before ball milling is 10~60min, the ball-to-material ratio during ball milling is 100:1, the ball milling speed is 50~1200rpm, and the ball milling time is 1~12h, so that the conductive carbon can fully wrap the alloy powder.

[0009] The electrolyte in S4 is a hydride electrolyte, and the ionic conductivity of the hydride electrolyte at 120°C is greater than 10 -3 S / cm, the mass ratio of mixed powder E to electrolyte is 3-9, the ball-to-material ratio used in ball milling is 100:1, the ball milling speed is 50-1200rpm, and the time is 1-12h.

[0010] The operating gas atmosphere of the above steps is high-purity argon.

[0011] In the alloy negative electrode prepared by the above method, the carbon particles of the conductive carbon uniformly wrap the silicon active material, and the active material, the solid electrolyte and the composite conductive carbon are interconnected to form a three-dimensional-tight electron / ion transmission network structure. The softer solid electrolyte and composite conductive carbon in the composite electrode can adapt to mechanical deformation and alleviate volume changes during the cycle.

[0012] Beneficial effects: The present invention provides an alloy negative electrode for a solid-state battery and a preparation method thereof. Compared with the prior art, the present invention has the following advantages: The alloy negative electrode of the present invention achieves a closer contact between lithium and silicon by pressing silicon powder, thereby achieving a better pre-lithiation effect and having a higher initial coulombic efficiency; at the same time, two conductive carbon additives are used in the electrode, and the matrix graphene material, as a typical two-dimensional material, is widely used in silicon-based negative electrodes due to its high specific surface area, excellent electronic conductivity, and excellent mechanical properties; based on the excellent performance of the second-phase conductive carbon, by using a composite conductive carbon additive, the conductive network inside the electrode can be complicated, the electron transmission path can be further improved, and the conductive network can be more closely combined with the active negative electrode, and the synergistic effect of the two conductive carbons is beneficial to improving electronic conductivity and reducing electrode polarization; at the same time, the composite conductive carbon can adapt to certain mechanical deformations, alleviate volume expansion, and can effectively alleviate the problems of too fast capacity drop and low cycle stability of the silicon electrode during the cycle. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 The figure is a comparison curve of the cycle discharge of the negative electrode obtained by the embodiment of the present invention and the comparative example; Figure 2 It is a comparative curve diagram of the rate discharge of the negative electrode obtained in the embodiment of the present invention and the comparative example; Figure 3 It is a polarization comparison curve diagram of the embodiment of the present invention and the comparative example. DETAILED DESCRIPTION

[0014] The present invention will be described in detail below with reference to specific embodiments and accompanying drawings: Example 1

[0015] A method for preparing a conductive carbon material coated alloy negative electrode comprises the following steps: S1. Press the nano-silicon powder into sheets through a 10 mm pressing die, and then press the lithium sheets into sheets and then coat them with silicon powder; heat treat the pressed samples at 250° C. for 30 min; grind the alloy powder sintered for the first time, and then heat treat it for the second time at 300° C. for 10 h; finally, heat treat the powder obtained from the second heat treatment for the third time at 300° C. for 10 h to obtain lithium silicon alloy powder; S2, graphene and conductive graphite were mixed in a mass ratio of 1:9, and after being evenly ground, they were ball-milled in a planetary ball mill at a ball-to-material ratio of 100:1 and a rotation speed of 1200 rpm for 12 h; S3, the alloy powder in S1 and the mixed conductive carbon obtained in S2 were mixed in a mass ratio of 2:1, and after being evenly ground, they were ball-milled in a planetary ball mill at a ball-to-material ratio of 100:1 and a rotation speed of 1200 rpm for 12 hours; S4. Add the powder obtained in S3 and the hydride electrolyte in a mass ratio of 3:1. After grinding evenly, mill in a planetary ball mill at a ball-to-material ratio of 100:1 and a rotation speed of 1200 rpm for 12 hours to obtain an alloy negative electrode. The above steps are all completed in a glove box filled with high-purity argon. Example 2

[0016] A method for preparing a conductive carbon material coated alloy negative electrode comprises the following steps: S1. Press the nano-silicon powder into sheets through a 10 mm pressing die, and then press the lithium sheets into sheets and then coat them with silicon powder; heat treat the pressed samples at 250° C. for 30 min; grind the alloy powder sintered for the first time, and then heat treat it for the second time at 300° C. for 10 h; finally, heat treat the powder obtained from the second heat treatment for the third time at 300° C. for 10 h to obtain lithium silicon alloy powder; S2, graphene and conductive graphite were mixed in a mass ratio of 0.1:9.9, and after being evenly ground, they were ball-milled in a planetary ball mill at a ball-to-material ratio of 100:1 and a rotation speed of 1200 rpm for 12 h; S3, the alloy powder in S1 and the mixed conductive carbon obtained in S2 were mixed in a mass ratio of 2:1, and after being evenly ground, they were ball-milled in a planetary ball mill at a ball-to-material ratio of 100:1 and a rotation speed of 1200 rpm for 12 hours; S4. Add the powder obtained in S3 and the hydride electrolyte in a mass ratio of 3:1. After grinding evenly, mill in a planetary ball mill at a ball-to-material ratio of 100:1 and a rotation speed of 1200 rpm for 12 hours to obtain an alloy negative electrode. The above steps are all completed in a glove box filled with high-purity argon. Example 3

[0017] A method for preparing a conductive carbon material coated alloy negative electrode comprises the following steps: S1. Press the nano-silicon powder into sheets through a 10 mm pressing die, and then press the lithium sheets into sheets and then coat them with silicon powder; heat treat the pressed samples at 250° C. for 30 min; grind the alloy powder sintered for the first time, and then heat treat it for the second time at 300° C. for 10 h; finally, heat treat the powder obtained from the second heat treatment for the third time at 300° C. for 10 h to obtain lithium silicon alloy powder; S2, graphene and conductive graphite were mixed in a mass ratio of 2:8, and after being evenly ground, they were ball-milled in a planetary ball mill at a ball-to-material ratio of 100:1 and a rotation speed of 1200 rpm for 12 h; S3, the alloy powder in S1 and the mixed conductive carbon obtained in S2 were mixed in a mass ratio of 2:1, and after being evenly ground, they were ball-milled in a planetary ball mill at a ball-to-material ratio of 100:1 and a rotation speed of 1200 rpm for 12 hours; S4. Add the powder obtained in S3 and the hydride electrolyte in a mass ratio of 3::1, grind evenly, and then mill in a planetary ball mill at a ball-to-material ratio of 100:1 and a rotation speed of 1200 rpm for 12 hours to obtain an alloy negative electrode. The above steps are all completed in a glove box filled with high-purity argon gas.

[0018] Comparative Example 1 The difference from the embodiment is that in the comparative example, only conductive graphite is used as a conductive additive, and the other steps are the same as the alloy negative electrode manufacturing method of the embodiment.

[0019] S1. Press the nano-silicon powder into sheets through a 10 mm pressing die, and then press the lithium sheets into sheets and then coat them with silicon powder; heat treat the pressed samples at 250° C. for 30 min; grind the alloy powder sintered for the first time, and then heat treat it for the second time at 300° C. for 10 h; finally, heat treat the powder obtained from the second heat treatment for the third time at 300° C. for 10 h to obtain lithium silicon alloy powder; S2, the alloy powder in S1 and the conductive graphite are mixed in a mass ratio of 2:1, and after being evenly ground, they are ball-milled in a planetary ball mill at a ball-to-material ratio of 100:1 and a rotation speed of 1200 rpm for 12 hours; S3. Add the powder obtained in S2 and the hydride electrolyte in a mass ratio of 3:1. After grinding evenly, mill in a planetary ball mill at a ball-to-material ratio of 100:1 and a rotation speed of 1200 rpm for 12 hours to obtain an alloy negative electrode. These steps are completed in a glove box filled with high-purity argon.

[0020] The alloy electrode prepared as above was used as the positive electrode, the lithium sheet was used as the negative electrode, and the hydride was used as the electrolyte, and the assembly was performed in a glove box filled with argon.

[0021] Then the alloy negative electrode||Li half-cell test was carried out. There are two test methods: (1) Cyclic charge and discharge: 20 cycles of constant current charging, charging and discharging at 0.1C, with a charging cut-off voltage of 1.5V and a discharging cut-off voltage of 0.1V.

[0022] Figure 1 This is the cycle curve of the alloy negative electrode under 0.1C conditions. When only conductive graphite is used as the conductive carbon, its 20-cycle capacity retention rate is 92.8%, and the first-cycle coulombic efficiency is 94.9%. When 0.5% graphene is added, the capacity retention rate is 99.2%, and the first-cycle coulombic efficiency is 99.6%. The capacity retention rate increased by 6.4%, and the first-cycle coulombic efficiency increased by 4.7%. It can be seen that the first-cycle coulombic efficiency and cycle performance of the electrode with the addition of two conductive additives are significantly improved.

[0023] (2) Rate charge and discharge: Discharge at 0.1C, 0.2C, 0.5C, 1C, and 2C, and charge at 0.1C. The charge cut-off voltage is 1.5V, and the discharge cut-off voltage is 0.1V.

[0024] Figure 2 This is the rate charge and discharge curve of the alloy negative electrode. Compared with the control sample, with the increase of current density, no significant polarization increase was observed in the half-cell using the composite additive, and it showed better rate performance, indicating that the use of the composite additive can effectively improve the utilization of active materials and reduce electrode polarization. The improvement in conductivity significantly improves the electrochemical performance of the silicon negative electrode at high rates.

[0025] (3) Polarization contrast: Figure 3 From the half-cell test curve when the alloy negative electrode is used as the positive electrode, it can be observed that when graphene and conductive graphite are used together as conductive carbon, the degree of polarization is significantly reduced compared to when conductive graphite is used alone, which indicates that the synergistic effect of graphene and conductive graphite effectively improves the conductivity and reaction kinetics of the electrode; in addition, the polarization values ​​of Examples 2 and 3 reach the lowest, further proving the significant advantages of the optimized conductive carbon combination in improving battery performance. This combination not only helps to reduce polarization, but also effectively improves the cycle stability and energy density of the battery, showing good application prospects.

[0026] The above-described embodiments are only preferred implementations of the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are all within the protection scope of the present invention.

Claims

1. A method for preparing an alloy negative electrode of a solid-state battery, characterized in that: The following steps are involved: S1, pre-lithiating silicon powder to obtain lithium-silicon alloy powder; S2, mixing the first conductive carbon and the second conductive carbon in a mass ratio of 0.01-0.25, and ball milling to obtain a conductive carbon mixed powder; S3, mixing the lithium silicon alloy powder and the conductive carbon mixed powder in a mass ratio of 2 to 8, and ball milling to obtain a mixed powder; S4. Add electrolyte to the mixed powder obtained in S3 at a mass ratio of mixed powder to electrolyte of 3-9, mix evenly, and ball-mill to obtain an alloy negative electrode.

2. The method for preparing an alloy negative electrode of a solid-state battery according to claim 1, characterized in that: The mass ratio of silicon to lithium is 2.3-4.

4.

3. The method for preparing an alloy negative electrode of a solid-state battery according to claim 1 or 2, characterized in that: During the pre-lithiation process of silicon powder, the first heat treatment heating temperature of lithium silicon alloy is 200~800℃, and the time is 15~60min; the second heat treatment heating temperature is 200~800℃, and the time is 1~10h; the third heat treatment heating temperature is 200~800℃, and the time is 1~10h.

4. The method for preparing the alloy negative electrode of the solid-state battery according to claim 3, characterized in that: The particle size of the silicon powder ranges from 10 to 250 nm.

5. The method for preparing the alloy negative electrode of the solid-state battery according to claim 1, characterized in that: The first conductive carbon is graphene.

6. The method for preparing an alloy negative electrode of a solid-state battery according to claim 1 or 5, characterized in that: The second conductive carbon is gas-phase carbon fiber, graphite or carbon nanotube.

7. The method for preparing the alloy negative electrode of the solid-state battery according to claim 1, characterized in that: The electrolyte is a hydride electrolyte, and the ionic conductivity of the hydride electrolyte at 120° C. is greater than 10 -3 S / cm.

8. The method for preparing the alloy negative electrode of the solid-state battery according to claim 1, characterized in that: The ball-to-material ratio used in ball milling is 100:1, the ball milling speed is 50~1200rpm, and the ball milling time is 1~12h.

9. The method for preparing the alloy negative electrode of the solid-state battery according to claim 1, characterized in that: All steps were carried out in a high-purity argon atmosphere.

10. A solid electrolyte alloy negative electrode, characterized in that: The carbon particles of the composite conductive carbon in the negative electrode uniformly wrap the silicon active material, and the silicon active material, the solid electrolyte and the composite conductive carbon are interconnected to form a three-dimensional and tight electron / ion transmission network structure.

Citation Information

Patent Citations

  • Self-supporting silicon negative electrode pre-lithiation preparation method and sulfide all-solid-state battery

    CN118448584A

  • Anode and cathode conductive additive for secondary lithium battery, method for preparing conductive additive, and method for preparing secondary lithium battery

    CN102544502A

  • Preparation method of nanocrystal lithium-rich single-phase Li-Si compound block material

    CN102699334A

  • Preparation of Li21Si5 and graphene composite material applied to lithium ion battery negative electrode

    CN108306002A

  • Lithium-silicon alloy negative electrode preparation method and sulfide all-solid-state battery

    CN114744161A

Cited By

  • Negative electrode material, preparation method thereof and secondary battery

    CN121583918A

  • Alloy ion / electron mixed conductor and application thereof

    CN121812280A